Implementing Social Determinants of Health (SDOH): A Technical Framework for Healthcare Systems Integration - Roja Rani Perumandla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores the integration of Social Determinants of Health (SDOH) into healthcare systems, focusing on implementation strategies across multiple domains. The article examines core screening methodologies, operational integration approaches, data systems architecture, community partnership development, financial models, and sustainability frameworks. The article highlights how integrated care management systems serve as critical technological infrastructure for operationalizing SDOH interventions, demonstrating how these platforms enable healthcare organizations to transform social screening data into actionable workflows, facilitate closed-loop referrals to community resources, and document outcomes required for value-based reimbursement models.Through analysis of various healthcare organizations’ experiences, the article demonstrates the effectiveness of standardized screening tools, structured care team models, and advanced data analytics in addressing social needs. The article emphasizes the importance of community partnerships, resource mapping, and value-based care integration in creating sustainable SDOH programs. Key articles highlight the significance of comprehensive performance metrics, continuous improvement protocols, and technology integration in achieving better health outcomes. The article mainly focuses on rural healthcare settings, examining how organizations can effectively implement SDOH programs while maintaining operational efficiency and regulatory compliance. This technical article provides healthcare organizations with structured approaches to integrate SDOH into their existing systems while emphasizing health equity and improved patient outcomes.